Moderasi Beragama di Kalangan Organisasi Keagamaan Islam - Syifa; Faridz (Yayasan Al-Afif, 2024)
This study aims to analyze in the literature related to religious moderation between Islamic religious organizations. This study uses the Systematic Literature Review (SLR) method with the stages of theme selection, search, literature selection, analysis and interpretation, preparation and dissemination of results. This study used 22 articles. The focus of the research includes three things, namely: (1) moderation of various perspectives of Nahdlatul Ulama, (2) religious moderation from the perspective of Muhammadiyah and (3) implementation of religious moderation. The results of the study show that both organizations have a strong commitment to religious moderation. NU emphasizes on the concepts of tasamuh, tawassuth and tawāzun, which are integrated through religious practices based on local traditions. Meanwhile, Muhammadiyah encourages religious moderation through new principles with a modern and rational approach. The implementation of religious moderation by NU and Muhammadiyah contributes to strengthening the harmony of the people and social stability in Indonesia.